A facile vesicle template route to multi-shelled mesoporous silica hollow nanospheres - Liu, Jian; Hartono, S.; Jin, Y.; Li, Z.; Lu, G.; Qiao, S. (The Royal Society of Chemistry, 2010)
Multi-shelled mesoporous silica hollow nanospheres (MMSHNs) with uniform size distribution (~150 nm), tuneable shell thickness (7–20 nm) and layer number (1–4 layers) have been successfully synthesized through a facile vesicle template approach derived from a self-assembly of surfactants [C3F7O(CFCF3CF2O)2CFCF3CONH(CH2)3N+(C2H5)2CH3I ] (FC4) and EO106PO70EO106 (F127). The formation of these hollow nanospheres was monitored by dynamic light scattering. A vesicle template mechanism for the molecular build-up of these silica hollow nanospheres was proposed based on the dynamic light scattering data in combination with material characterizations including transmission electron microscopy (TEM), scanning electron microscopy (SEM) and nitrogen sorption analysis. Through this method, CdTe quantum dots (QDs) were in situ encapsulated into the hollow nanospheres. These hollow nanospheres demonstrated a good selective adsorption capacity for Methylene Blue dye, and can effectively load drug molecules for delivery. It is expected these hollow nanospheres have great potential for the application in fluorescence biological probes, bio-imaging, drug delivery and water purification.